Predictors of Variation in Role Performance of Scientists Working in KVKs - Bellagi, Rahul Dundesh; Patel, H. B.; Chethan Patil, N.D.; G., Manunayaka; V, Pavithra (Indian Journal of Extension Education, 2020)
Role performance is in reality not influenced by any of the independent variable singly. It is found to be influenced by more than one of these independent attributes jointly through their reciprocal and interactive relationship. The study on scientists working in KVKs (Krishi Vigyan Kendra) of Gujarat was carried out considering all 30 KVKs in the state. A total of 97 responses were collected through mailed questionnaire whichÂ includes 11 independent variables. Achievement motivation, job stress and training received were predicted toÂ account for more variation in their role performance.